6n+3=5+6n-2

Simple and best practice solution for 6n+3=5+6n-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n+3=5+6n-2 equation:


Simplifying
6n + 3 = 5 + 6n + -2

Reorder the terms:
3 + 6n = 5 + 6n + -2

Reorder the terms:
3 + 6n = 5 + -2 + 6n

Combine like terms: 5 + -2 = 3
3 + 6n = 3 + 6n

Add '-3' to each side of the equation.
3 + -3 + 6n = 3 + -3 + 6n

Combine like terms: 3 + -3 = 0
0 + 6n = 3 + -3 + 6n
6n = 3 + -3 + 6n

Combine like terms: 3 + -3 = 0
6n = 0 + 6n
6n = 6n

Add '-6n' to each side of the equation.
6n + -6n = 6n + -6n

Combine like terms: 6n + -6n = 0
0 = 6n + -6n

Combine like terms: 6n + -6n = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 6x+6=-15 | | x^2-2x-1.1=0 | | -32-5x=4x+12 | | -3-4x=-9 | | 3x^2+15x+12= | | 7y+14=21x | | 10x-126=14x+35 | | -14-7x=-3 | | -5.5=-0.02x^2+x+0.5 | | -5.5=-0.02x+x+0.5 | | 5(n+7)=-44+2(n+6) | | y=-0.02x^2+x+0.5 | | 2x+7-3x=1 | | y=-0.02x+x+0.5 | | 3x+27=10x-33 | | -40=33x+15 | | 3=-x+1 | | 6(2x+1)-3(5x+2)=0 | | 8=8n-22-7n | | -x+3= | | y=-0.02x+x+6 | | 7=3(x-7)+10 | | 8x=16(x-36) | | x=-5+4 | | 3x+15=6x+7 | | 3(2-a)=8-a | | 3x-8=5(2x-3) | | 147-4x=23x+21 | | 5x=(6x-3) | | 5(2x-3)+6=43-3x | | 8+12x=15x-19 | | 2c+5=3c+7 |

Equations solver categories